RISIKO BAHAYA ERGONOMI PETUGAS KEBERSIHAN OUTSOURCING DI RUMAH SAKIT UMUM DAERAH SLEMAN - Diki Bima Prasetio (Jurnal Kesehatan Masyarakat Indonesia, 2015)
Background: The cleaning service have special physical demands of each to do his job, the most significant risk factors associated with physical work load is static, repetitive motion and muscle strength requires high in doing his job. Purpose:Analyze the risk of ergonomic hazard cleaning service outsourcing in Sleman Hospital.Methods:A descriptive case study with the study design a holistic single case design. Key informants consists of two cleaning service, director, head of sanitary installations and secretary of the committee occupational safety and health.Results:Cleaning Service at risk of harm caused by ergonomic factors such as disease, musculoskeletal disorders. The absence of support from hospital management of occupational safety and health cleaning service because all responsibility has been given to the providers of laborConclusions:The hospital management has not given the same opportunity to the cleaning service as other hospital employees about occupational safety and healthto obtain ergonomic hazards that have long-term effects of the disease musculoskeletal disorders.